1998
DOI: 10.1073/pnas.95.16.9642
|View full text |Cite
|
Sign up to set email alerts
|

Desoxyepothilone B: An efficacious microtubule-targeted antitumor agent with a promising in vivo profile relative to epothilone B

Abstract: A new class of 16-membered macrolides, the epothilones (Epos), has been synthesized and evaluated for antitumor potential in vitro and in vivo. Recent studies in these and other laboratories showed that epothilones and paclitaxel (paclitaxel) share similar mechanisms of action in stabilizing microtubule arrays as indicated by binding-displacement studies, substitution for paclitaxel in paclitaxel-dependent cell growth, and electron microscopic examinations. The present study examined cell growth-inhibitory eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
143
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 199 publications
(147 citation statements)
references
References 16 publications
3
143
0
1
Order By: Relevance
“…Another classical example is the identification of the secondary metabolites, epothilones (microtubule depolymerization inhibitors) of the myxobacterium Sorangium cellulosum, which have shown both in vitro and in vivo cytotoxicity in various cancer cells. 38,39 Epothilones are anti-microtubule agents, and their mechanism of action is more or less similar to taxol. However, epothilones have several advantages over taxol.…”
Section: Bacteria-derived Anti-cancer Agentsmentioning
confidence: 99%
“…Another classical example is the identification of the secondary metabolites, epothilones (microtubule depolymerization inhibitors) of the myxobacterium Sorangium cellulosum, which have shown both in vitro and in vivo cytotoxicity in various cancer cells. 38,39 Epothilones are anti-microtubule agents, and their mechanism of action is more or less similar to taxol. However, epothilones have several advantages over taxol.…”
Section: Bacteria-derived Anti-cancer Agentsmentioning
confidence: 99%
“…Lin et al (15) have tested patupilone (epothilone B) in an s.c. RPMI 8226 MM xenograft mouse model and showed a modest prolongation of survival. Because of its high toxicity, the clinical application of epothilone B is limited (33,34). Our in vivo data in both subcutaneous and disseminated MM xenograft models showed Flu to be much more effective than dEpoB.…”
Section: Discussionmentioning
confidence: 79%
“…By contrast, adriamycin, paclitaxel, and vinblastine exhibited only partial suppressive effects. These results provide a differential perspective on our initial findings (19,27,28), in which dEpoB showed comparable efficacy to paclitaxel in several sensitive tumors but proved superior over paclitaxel in a broad range of drug-resistant tumors (e.g., tumors resistant to VBL, Adr, or paclitaxel). The striking difference presented by these experiments suggests that even sensitive tumors can be more responsive to dEpoB than conventional anticancer agents.…”
Section: Therapeutic Efficacy Of Various Anticancer Agents Against Humanmentioning
confidence: 86%
“…Pharmacological evaluations in xenograft mouse models revealed that EpoB, although the most potent drug in the epothilone series, possessed poor therapeutic efficacy at its maximal-tolerated dose (19). In contrast, we discovered that 12,13-desoxyepothilone B (dEpoB) displays a much more promising therapeutic index despite its slightly decreased in vitro cytotoxicity relative to EpoB (19,20).…”
mentioning
confidence: 81%
See 1 more Smart Citation